Implementasi Kaizen Dan 5S Pada Pengeringan Produk Di Proses Plating - Soesilo, Rahman (Jurnal Teknik Industri, 2017)
Innovation can be made of small things in our routine activities. Â Seiri (sort), Seiton (set in order), Seiso (shine), Seiketsu (standards), and Shitsuke (sustain) is 5 words in Japanese, which is a systematic technique in correlation with efficiency. Kaizen has been widely known in the world as continuous improvement through small steps that affect the economy of the company. This system helps the management to manage the workplace, improve discipline, reduce waste and increase productivity. NGK Busi Indonesia is one of the companies owned by the Japanese spark plug that upholds the quality control contributed significantly to the implementation of Kaizen and 5S. This study explores the innovative implementation of 5S Kaizen refers to that applied in the productionÂ  floor. Direct observation was made as basic methodology of this study. PT NGK Busi Indonesia always fix some work through Kaizen techniques to improve efficiency.